PENGARUH PEMBERIAN PENGUATAN (REINFORCEMENT) DI MASA COVID-19 TERHADAP HASIL BELAJAR SISWA KELAS V SD NEGERI 054870 TANJUNG JATI KEC. BINJAI - Juwita Tindaon; Eti Muliani (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: The Effect of Reinforcement During the Covid-19 Period on the Learning Outcomes of Class V Elementary School Students at State 054870 Tanjung Jati Kec. Binjai, this research was conducted at the State Elementary School 054870 Tanjung Jati Kec. Binjai, who became the sample in this study were students of class V, totaling 30 students. The purpose of this study was to determine whether there was an effect of providing reinforcement during the Covid-19 period on the learning outcomes of fifth graders at the State Elementary School 054870 Tanjung Jati Kec. Binjai Kab. Langkat. The type of research carried out is quasi- experimental, namely research that aims to determine the provision of reinforcement (reinforcement) with the learning outcomes of class V students. Data analysis used using the Product Moment Correlation formula. Based on the analysis of the data, it was found that the description of the provision of reinforcement at the State Elementary School 054870 Tanjung Jati was in the fairly good category, because of the 30 students, 13 students stated that the provision of reinforcement was in the good enough category. While the description of the learning outcomes of Citizenship Education of Class V students is in the good category, because the average value of Citizenship Education learning outcomes for Class V students is76.71 and is in the good category. So that the results of student interest in class V Elementary School 054870 Tanjung Jati are in the good category. For the correlation test, the t value is 27.08 while the t in the table is 2.05 so that the t count is greater than t in the table, so there is a significant influence between the provision of reinforcement in the Covid-19 Period on the Learning Outcomes of Class V State Elementary School Students 054870 Tanjung Jati District. Binjai. Keywords: Giving Reinforcement and Civics Learning Outcomes Abstrak: Pengaruh Pemberian Penguatan (Reinforcement) Di Masa Covid-19 Terhadap Hasil Belajar Siswa Kelas V SD Negeri 054870 Tanjung Jati Kec. Binjai, penelitian ini dilaksanakan di SD Negeri 054870 Tanjung Jati Kec. Binjai, yang menjadi sampel dalam penelitian ini adalah siswa kelas V yang berjumlah 30 orang siswa. Adapun tujuan dalam penelitian ini adalah untuk mengetahui apakah ada pengaruh pemberian penguatan (reinforcement) di masa covid-19 terhadap hasil belajar siswa kelas V SD Negeri 054870 Tanjung Jati Kec. Binjai Kab. Langkat. Jenis penelitian yang dilakukan adalah quasi eksperimen, yaitu penelitian yang bertujuan untuk mengetahui pemberian penguatan (reinforcement) dengan hasil belajar siswa kelas V. Analisis data yang digunakan menggunakan rumus Kolerasi Product Moment. Berdasarkan analisis data diperoleh gambaran pemberian penguatan di SD Negeri 054870 Tanjung Jati masuk dalam kategori cukup baik, karena dari 30 orang siswa 13 orang siswa menyatakan kalau Pemberian Penguatan masuk dalam kategori cukup baik. Sedangkan gambaran hasil belajar PKn Siswa Kelas V masuk dalam kategori baik, karena dari nilai rata-rata hasil belajar PKn siswa Kelas V 76,71 dan masuk dalam kategori baik. Sehingga hasil minat belajar siswa kelas V SD Negeri 054870 Tanjung Jati masuk kategori baik. Untuk uji kolerasi diperoleh nilai t adalah 27,08 sedangkan t dalam tabel adalah 2,05 sehingga t hitung lebih besar dari t dalam tabel maka ada pengaruh yang signifikan antara pemberian penguatan Di Masa Covid-19 Terhadap Hasil Belajar Siswa Kelas V SD Negeri 054870 Tanjung Jati Kec. Binjai. Kata Kunci: Pemberian Penguatan dan Hasil Belajar PKn